2022
DOI: 10.15626/mp.2021.2803
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Findings of the Self-Controlled Motor Learning Literature: Underpowered, Biased, and Lacking Evidential Value

Abstract: The self-controlled motor learning literature consists of experiments that compare a group of learners who are provided with a choice over an aspect of their practice environment to a group who are yoked to those choices. A qualitative review of the literature suggests an unambiguous benefit from self-controlled practice. A meta-analysis was conducted on the effects of self-controlled practice on retention test performance measures with a focus on assessing and potentially correcting for selection bias in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 124 publications
(124 reference statements)
1
11
0
Order By: Relevance
“…When power analyses were reported, they were rarely reproducible without making assumptions, and even then, most power analyses could not be reproduced. Meanwhile, there is growing evidence that the average power among motor behavior studies is low, making the literature vulnerable to more severe bias from various selective reporting mechanisms (e.g., Lohse et al, 2016;McKay, Yantha, et al, 2022;Mesquida et al, 2022). Here, we argue that power analyses can easily be reported in a reproducible fashion and doing so is a progressive step toward improved research quality overall.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…When power analyses were reported, they were rarely reproducible without making assumptions, and even then, most power analyses could not be reproduced. Meanwhile, there is growing evidence that the average power among motor behavior studies is low, making the literature vulnerable to more severe bias from various selective reporting mechanisms (e.g., Lohse et al, 2016;McKay, Yantha, et al, 2022;Mesquida et al, 2022). Here, we argue that power analyses can easily be reported in a reproducible fashion and doing so is a progressive step toward improved research quality overall.…”
Section: Discussionmentioning
confidence: 85%
“…A lack of thoroughly reported and vetted power analyses contributes to the proliferation of underpowered studies, which combined with selection for significant results threatens the credibility of our literature. The impact of low power and selection bias is well illustrated by the growing body of metascience calling into question the reliability of research paradigms long considered robust (Carter et al, 2015;e.g., Maier et al, 2022;Vohs et al, 2021), such as self-controlled practice in the motor learning domain (McKay, Yantha, et al, 2022). In a recent metaanalysis, McKay and colleagues estimated the benefit to motor learning of giving learners control over an aspect of their environment is trivially small, if existent, after correcting for publication bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on motor behavior research as recent meta-analyses have reported evidence of both underpowered research and substantial reporting bias in motor learning and sports science (Lohse et al, 2016;2022a, b;Mesquida et al, 2022). For example, a meta-analysis of the self-controlled motor learning literature estimated the average power of all studies conducted was 6%, while 48% of studies reported significant results on the focal measure (McKay et al, 2022b). Other studies have estimated average power ranging from 20% (McKay et al, 2022a) to 50% (Mesquida et al, 2022), with significant indications of reporting bias.…”
mentioning
confidence: 99%